Pembelajaran Moderasi Beragama Pada Tingkat Usia Dasar - Harahap, Muhammad Rifai (Prodi PGMI STIT Al-Ittihadiyah Labuhanbatu Utara, 2024)
This study aims to analyze religious moderation learning strategies at the Madrasah Ibtidaiyah level, specifically at MIS Kuba, as well as the challenges faced in its implementation. Based on the research findings, it was found that the learning strategies implemented include a contextual approach in teaching the Qur'an and hadith, the use of discussion methods, the utilization of digital media, and the integration of religious moderation values in extracurricular activities. These strategies have successfully improved students' understanding of tolerance, respect for differences, and the application of moderate values in daily life. However, challenges include time constraints, difficulties in accessing digital media due to infrastructure issues, and the influence of conservative social and family backgrounds. This study makes an important contribution to the development of religious moderation education in Madrasah Ibtidaiyah by providing new insights into strategies that can be implemented and challenges that must be addressed. The findings of this study are expected to serve as a reference in designing a more adaptive and applicable curriculum for teaching religious moderation to students at the elementary level.